Homoeopathic Management of Benign Prostatic Hypertrophy - Case Reports (Advancements in Homeopathic Research, 2022)
Benign prostatic hypertrophy or benign prostatic hyperplasia (BPH) is a condition that occurs due to proliferation of cells of prostatic gland. BPH is most commonly seen in elderly men.Benign hyperplastic changes may start at 45 years. Most of the research studies proved that homoeopathy is having more significant action over genitourinary diseases especially in case of diseases like benign hypertrophy of prostate (BHP). Even in surgical cases when the patient is treated with principles of homoeopathy, permanent cure is attained. This case report presents 4 cases of BPH which improved symptomatically. The Urinary tract consists of kidneys, ureters, bladder and urethra.1Prostate is an organ of male which is situated around the urethra. Benign prostatic hypertrophy or benign prostatic hyperplasia (BPH) is a condition that occurs due to proliferation of prostatic gland cells.2 It is a non malignant condition. BPH is most commonly seen in elderly men. Benign hyperplastic changes may start at 45 years. Age incidence of BPH is usually between 45-50, can present up to 75 years among 75% in total male population. 3,4,5Aetiology for prostatic enlargement is unknown till now, even though hormonal changes in elderly men is believed as one of the reason.3
Keywords: (BPH); (BHP); Prostatic Hypertrophy; cystourethroscopy; uroflowmetry; urography